Contribution to a standardized economic and ecological assessment methodology for e-fuel production in Germany - Heimann, Nathanael; Raab, Moritz; Wulff, Niklas; Haas, Sofia; Pichlmaier, Simon; Dietrich, Ralph-Uwe (Frontiers in Energy Research, 2025)
Techno-economic and ecological analysis of synthetic fuel production requires a consistent set of assumptions to ensure comparability. The proposed methodology was developed to assess any e-fuel production globally under various local conditions. It includes standards concerning the methodology and cost calculations for individual process stages, along with electricity, H2, heat, and CO2 supply. With the presented approach, net production costs, production efficiencies, and the global warming potential can be compared. In this work, the basic assumptions for e-fuel-production in Germany are shared and illustrated with a simplified example.